ISOLASI, IDENTIFIKASI 16S rRNA DAN KARAKTERISASI MORFOLOGI BAKTERI PENDEGRADASI PLASTIK POLIETILEN (PE) - Norma Sainstika Pangestu; Anto Budiharjo; MG Isworo Rukmi (Jurnal Akademika Biologi, 2016)
Plastic waste is one of the environmental issues that still need to be handled properly. plastic  commonly  used  are  basically  formed  by  polyethylene  which  is  contains  chemical compound.  Less cavity of plastic can disturb soil aeration which is important for other aerobic organism. This problem lead to increasing ecological threat. The main objective of present study is to isolate the soil microorganism that have a role as an agent  through plastic degradation. Bacteria were isolated from the surface of the plastic which is buried in soil. The  isolation is been carried out through soil serial dilution method and inoculated into selective King’s B agar. Isolates were obtained and then tested the ability of degradation of the PE. Isolates with the highest degradation  activity isolates G then identified using molecular methods based on 16S rRNA. the results showed that the 16S rRNA sequencing isolates G measuring 1,500 bp with the highest homologous species derived from the genus Bacillus. Keywords: Polyethylene, bacteria, biodegradation